Do burned-out and work-engaged employees differ in the functioning of the hypothalamic-pituitary-adrenal axis? - Langelaan, Saar; Bakker, Arnold B.; Schaufeli, Wilmar B.; van Rhenen, Willem; van Doornen, Lorenz JP (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'The central aim of the present study was to examine differences in the functioning of the hypothalamic-pituitary-adrenal (HPA) axis between 29 burned-out, 33 work-engaged, and 26 healthy reference managers, as identified with the Maslach Burnout Inventory-General Survey and the Utrecht Work Engagement Scale. ' ' METHODS ': 'All of the managers were employed in a large Dutch telecommunications company. Salivary cortisol was sampled on three consecutive workdays and one nonworkday to determine the cortisol awakening response. Salivary dehydroepiandrosterone-sulfate (DHEAS), a cortisol counterbalancing product of the HPA axis, was measured on these days 1 hour after managers awakened. The dexamethasone suppression test was used to investigate the feedback sensitivity of the HPA axis. ' ' RESULTS ': 'The morning cortisol levels were higher on the workdays than on the nonworkday, but this effect did not differ between the three groups. The burned-out, work-engaged, and reference groups did not differ in the cortisol and DHEAS levels, the slope of the cortisol awakening response, and the cortisol : DHEAS ratio. The work-engaged group showed a stronger cortisol suppression in response to the dexamethasone suppression test than the other two groups, the finding suggesting higher feedback sensitivity among work-engaged managers. ' ' CONCLUSIONS ': 'Burned-out and work-engaged managers only differ marginally in HPA-axis functioning.
Keywords: burned-out employee; burnout; cortisol awakening response; dehydroepiandrosterone-sulfate; dexamethasone suppression test; function; hypothalamic-pituitary-adrenal axis; work engagement; work-engaged employee